2015
DOI: 10.1038/srep16481
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the binding modes and the unbinding of 14-3-3σ proteins and inhibitors by computational methods

Abstract: The 14-3-3σ proteins are a family of ubiquitous conserved eukaryotic regulatory molecules involved in the regulation of mitogenic signal transduction, apoptotic cell death, and cell cycle control. A lot of small-molecule inhibitors have been identified for 14-3-3 protein-protein interactions (PPIs). In this work, we carried out molecular dynamics (MD) simulations combined with molecular mechanics generalized Born surface area (MM-GBSA) method to study the binding mechanism between a 14-3-3σ protein and its eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…For each trajectory, we extracted 500 snapshots from the last 50 ns of the MD trajectories with an interval of 100 ps. Briefly, the MM-PBSA method was used to calculate the binding free energies using the following equations [64,65]:…”
Section: Binding Free Energy Calculationsmentioning
confidence: 99%
“…For each trajectory, we extracted 500 snapshots from the last 50 ns of the MD trajectories with an interval of 100 ps. Briefly, the MM-PBSA method was used to calculate the binding free energies using the following equations [64,65]:…”
Section: Binding Free Energy Calculationsmentioning
confidence: 99%
“…In the MM-PSA, a series of representative snapshots from MD trajectories were collected to incorporate the effects of thermal averaging with force field/continuum solvent models. [ 15 ]. Compared with rigorous methods such as free energy perturbation (FEP), MM-PBSA is more computationally efficient [ 16 ].The MM-PBSA method was developed by Kollman et al [ 17 ] and has been widely used ever since, with more than 100 publications each year from 2010 to now [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their virtual docking into a high-resolution crystal structure of 14-3-3σ (PDB ID: 3P1N) and follow-up analysis led to the synthesis and cocrystallization of 11 14-3-3 inhibitors (e.g., compound B2 (19, Figure 12)). 138 A detailed computational analysis of the binding mode of eight of these molecules was performed by the group of Wang et al 139 They showed that the hydrophilic residues (Arg56, Arg129, and Tyr130 of 14-3-3σ) at the bottom of the binding pocket form seven stable hydrogen bonds with the phosphate group. In addition, two residues (Leu174 and Val178) in contact with a moiety accommodating the phosphate group contribute large van der Waals energies, and residue Leu126 provides large electrostatic energies.…”
Section: 137mentioning
confidence: 99%